Macroeconomic analysis of monetary unions a general framework based on the Mundell-Fleming Model - Bajo-Rubio, Oscar; Díaz-Roldán, Carmen (SpringerBriefs in Economic, 2011)
The book develops a general framework for the macroeconomic modeling of monetary unions. The starting point of the analysis is the standard two-country Mundell-Fleming model with perfect capital mobility, extended to incorporate the supply side in a context of rigid real wages, and modified so that the money market is common for two countries forming a monetary union. The model is presented in two versions: for a small and a large monetary union, respectively. After solving each model, the authors derive multipliers for monetary, expenditure, supply, and external shocks, both in the short and the long run; a graphical analysis is also provided. Special attention is paid to the crucial distinction between symmetric and asymmetric shocks